Effects of micronutrient application on different attributes of potato in floodplain soils of Bangladesh (SAARC Journal of Agriculture, 2019)
Different crops have variations in their responses to applied micronutrients in soil. A study was conducted on floodplain soil of Bangladesh to explore the response of potato to application of micronutrients in soil. The experimental site was located at farmers’ field in Chandina upazila under Cumilla district of Bangladesh covering the soils of Old Meghna Estuarine Floodplain (AEZ 19) during 2011-12. Randomized complete block design with 3 replications of each treatment was used in the experiment, where seven treatments including a control were tested. Additive element trial technique was followed while designing the treatments taking six micronutrients i. e. Zn, B, Cu, Mn, Fe and Mo at the rate of 3, 2, 2, 3, 5 and 1 kg ha-1, respectively. Macronutrients, such as N, P, K and S were applied at recommended rates to all plots. The highest tuber yield (28.7 t ha-1) was produced by the combined application of Zn and B. Only Zn application was sufficient to obtain the highest content of protein as well as content of almost all the nutrients in potato tuber. Antagonistic relation between Zn and P in soil-plant system was recorded in the study. Zinc and boron application influenced different growth and yield parameters of potato while the other four added micronutrients did not have any significant effect but combined application of Zn, B, Cu, Mn, Fe and Mo had beneficial role for better plant growth and production. Proper management of zinc and boron fertilizers including optimization of application rates of those nutrients can help to uphold the yield and quality of potato in floodplain soil.SAARC J. Agri., 16(2): 97-108 (2018)